Wagering demonstrates subconscious processing in a binary exclusion task. - Persaud, N; McLeod, P (2008)
We briefly presented either the letter 'b' or the letter 'h' to participants who were instructed to respond by saying the letter that was not shown. This binary version of the exclusion task avoids problems with assessing baseline completion rates. When the letters were shown for 5-10 ms participants erroneously responded with the shown letter at a rate greater than chance. They were capable of following the instructions when the letter was shown for longer (15 ms). Given the chance to wager low or high on their choices after short duration stimuli, participants declined to wager high even when they were correct. Taken together these results suggest that the briefly presented stimuli were processed subconsciously.